A Fast Shift-Splitting Iteration Method for Nonsymmetric Saddle Point Problems. Issue 1 (31st January 2017) - Dou, Quan-Yu; Yin, Jun-Feng; Liao, Ze-Yu
Abstract: Based on the shift-splitting technique and the idea of Hermitian and skew-Hermitian splitting, a fast shift-splitting iteration method is proposed for solving nonsingular and singular nonsymmetric saddle point problems in this paper. Convergence and semi-convergence of the proposed iteration method for nonsingular and singular cases are carefully studied, respectively. Numerical experiments are implemented to demonstrate the feasibility and effectiveness of the proposed method.